PENGARUH PENYULUHAN MEDIA WAYANG KERTAS TERHADAP PENGETAHUAN KESEHATAN GIGI DAN MULUT PADA MURID KELAS III DI MIN 14 BANJAR - Anggraini, Noviathul; Amperawati, drg. Metty; Danan (Poltekkes Kemenkes Banjarmasin, 2022)
Efforts to increase knowledge can be done with health education. One of the effective dental health maintenance efforts is dental and oral health counseling, especially for children, so that health education efforts to target school children are the first and main priority. The paper puppet media was chosen because the puppet game is easy to adapt in its use in elementary schools, effective in increasing children's knowledge and paper puppet media as well as alternative media in learning. This study aims to determine the effect of using paper puppet media on dental and oral health knowledge. The design in this study used the One Group pretest posttestʼʼ design. This type of research is a quasi-experimental (quasi-experimental). Analyzed using Paired Sample T-Test. The research sample was 57 students in class IIIA and IIIB. The sampling technique used was total sampling. The results of the study of dental and oral health knowledge before counseling on paper puppet media were 9.47 and after counseling 13.47. These results indicate a change in the value of 4. Based on the Paired Sample T-Test test, the value (p) is 0.000, so it is smaller than alpha (ɑ) = 0.05 so it can be concluded that p < , thus Ho is rejected and Ha accepted. The conclusion is that there is an influence of paper puppet media counseling on dental and oral health knowledge in third grade students at MIN 14 Banjar. It is suggested that promotive activities need to be held, namely continuous counseling at the school in order to help students understand health, especially on dental and oral health problems.